Cellulose Production of Uzbekistan Release Raw Material - Shaymanova, R.S.; Urazov, M.K.; Yuldosheva, D.N. (International Journal on Orange Technologies, 2022)
The Republic of Uzbekistan has unlimited opportunities in the study of cellulose, as well as in its production and processing.